PERENCANAAN STRATEGIK BERPARADIGMA ISLAM - S l a m e t, S l a m e t (IQTISHODUNA, 2009)
The paper, which is part of the chapter of a recently completed dissertation in the field of strategic management of information system, deals with the strategic planning base on Islamic paradigm. Strategic planning base on Islamic paradigma is responses from the conventional strategic planning concept. The strategic planning base on Islamic paradigm is the planning concept in an organization which is comprehensively carried out along with the Islamic values and principles. The strategic planning base on Islamic paradigm has five main stages: (1) to develop a strategic planning initiative (why) whose purpose is to provide an answer to the question â€œwhy we initiate the planningâ€; (2) to determine the direction of the organizationalÂ  goals (what), which is intended to answer the question of what is to be achieved by an organization in the future; (3) to assess and analyze the organizational environment (where), whose objective is to identify and understand the real position of the organization and simultaneously identify the factors that affect the achievement of organizational goals; (4) toÂ  chose as well as determine alternative strategies (how), which is designed to answer the question of how or what strategies can be used in achieving organizational goals; and (5) to develop a design implementation (when). The last point is to answer the question of when the program can be run based on the strategy set.